If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -36 + -33y + 30y + -32y + 11y = 31y + -24 + 16y Combine like terms: -33y + 30y = -3y -36 + -3y + -32y + 11y = 31y + -24 + 16y Combine like terms: -3y + -32y = -35y -36 + -35y + 11y = 31y + -24 + 16y Combine like terms: -35y + 11y = -24y -36 + -24y = 31y + -24 + 16y Reorder the terms: -36 + -24y = -24 + 31y + 16y Combine like terms: 31y + 16y = 47y -36 + -24y = -24 + 47y Solving -36 + -24y = -24 + 47y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-47y' to each side of the equation. -36 + -24y + -47y = -24 + 47y + -47y Combine like terms: -24y + -47y = -71y -36 + -71y = -24 + 47y + -47y Combine like terms: 47y + -47y = 0 -36 + -71y = -24 + 0 -36 + -71y = -24 Add '36' to each side of the equation. -36 + 36 + -71y = -24 + 36 Combine like terms: -36 + 36 = 0 0 + -71y = -24 + 36 -71y = -24 + 36 Combine like terms: -24 + 36 = 12 -71y = 12 Divide each side by '-71'. y = -0.1690140845 Simplifying y = -0.1690140845
| x^2+19=10x | | 7b=-56 | | 4x^2+20x+4y^2+8y-115=0 | | 2(4c-1)-4=4c+2 | | -2(u-8)=-5u+34 | | -2.5+1.5x=3+2x | | y=1/2x+5 | | 39y+14+3y=21-25y-35y-13-18y+36y | | y=4x(x-3)-4x^2 | | 6(y+1)+8y=2(y-3) | | 3.2/3 | | -2-1=x+11 | | -x^2+2(3.14)x-33=0 | | -2x-18x+33=-7 | | -19-40y+19y=22-33y+31+29y-34y | | 2+(-3)= | | 9x^2-88x=0 | | 8-3x+15=-2x | | log(x)-log(x-3)=3 | | 26x^3y^4z^2+14x^2y^6=2x^2y^4z^2(13x+7y^2z^2) | | -21-7x=-(-28x+6)-8 | | X^4+10x^3+4x^2+4x+27=0 | | logx-log(x-3)=3 | | -x/3=5 | | 5x^2+4x-9= | | 3x^4+11x^3-4x^2+0x+0=0 | | 26x^3y^4z^2+14x^2y^6=2x^2y^4(13xz^2+7y^2) | | 5b+16=-3b | | 7x+14-6x=-5-12 | | 5x+130=15x-10 | | -27y-33-25y=-17-20y-15y-38y | | (x+3)+(x+3)+(x+3)+x=73 |